The politics of accountability in Southeast Asia the dominance of moral ideologies - Rodan, Garry 1955-; Hughes, Caroline 1969- (Oxford studies in democratization., 2014)
This volume examines different ideologies and related political coalitions forming the bases of movements for accountability reform in Southeast Asia.